2021
DOI: 10.3390/nano11061533
|View full text |Cite
|
Sign up to set email alerts
|

Triboelectric Energy Harvester Based on Stainless Steel/MoS2 and PET/ITO/PDMS for Potential Smart Healthcare Devices

Abstract: The smart healthcare devices connected with the internet of things (IoT) for medical services can obtain physiological data of risk patients and communicate these data in real-time to doctors and hospitals. These devices require power sources with a sufficient lifetime to supply them energy, limiting the conventional electrochemical batteries. Additionally, these batteries may contain toxic materials that damage the health of patients and environment. An alternative solution to gradually substitute these elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Figure 3 d(i–v) demonstrates a working cycle of the MSSAS [ 26 , 27 ]. In the static state, the internal vibrating column is suspended in the MSSAS under the action of eight springs.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 d(i–v) demonstrates a working cycle of the MSSAS [ 26 , 27 ]. In the static state, the internal vibrating column is suspended in the MSSAS under the action of eight springs.…”
Section: Resultsmentioning
confidence: 99%
“…Among these 2D semiconductors, MoS 2 is the most investigated in TENGs. MoS 2 materials can act solely , as a triboelectric layer for energy conversion or be composited with other polymers. The output power densities of the MoS 2 constituted TENGs range from 74 nW/cm 2 to 50 mW/cm 2 , while the open-circuit voltage ranges from 2.3 to 145 V. The highest output, 50 mW/cm 2 , is from a TENG with both triboelectric layers composited with MoS 2 flakes and polarized afterward (Figure ).…”
Section: Inorganic Nanomaterials Used In Tengsmentioning
confidence: 99%
“…Several studies have investigated negative contact materials based on MoS 2 in TENGs. [28][29][30][31] Moreover, Wu et al suggested using MoS 2 as an electron trap material below negative contact material with high efficiency and outstanding outputs. [16] Currently, TENGs have been suggested to be employed in various fields.…”
Section: Introductionmentioning
confidence: 99%